2001
DOI: 10.1038/modpathol.3880303
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection, Centrosome Aberration, and Genetic Stability in Cervical Lesions

Abstract: DNA replication and centrosome duplication have to be strictly synchronized to guarantee genomic stability. p53, pRb, cyclin E, and cyclin A are reported to be involved in the synchronizing process. We investigated the relationship between papillomavirus infection, centrosome aberration and aneuploidy during genesis of cervical carcinoma. The number of centrosomes found in cells from normal cervical epithelium (n ‫؍‬ 5), condyloma acuminata (n ‫؍‬ 5), cervical intraepithelial neoplasia (CIN) I, II, and III (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…We found that scattering of DNA profiles as a measure of genomic instability correlates highly significantly with centrosome aberrations. While centrosome abnormalities have been reported earlier in different human malignancies (Pihan et al, 1998;Ghadimi et al, 2000;Skyldberg et al, 2001;Roshani et al, 2002), including breast cancer (Lingle et al, 1998;Lingle and Salisbury, 1999), a difference in the extent of centrosome aberrations in cytometrically determined subtypes of breast carcinomas has, to our knowledge, not been reported by other authors.…”
Section: Discussioncontrasting
confidence: 43%
“…We found that scattering of DNA profiles as a measure of genomic instability correlates highly significantly with centrosome aberrations. While centrosome abnormalities have been reported earlier in different human malignancies (Pihan et al, 1998;Ghadimi et al, 2000;Skyldberg et al, 2001;Roshani et al, 2002), including breast cancer (Lingle et al, 1998;Lingle and Salisbury, 1999), a difference in the extent of centrosome aberrations in cytometrically determined subtypes of breast carcinomas has, to our knowledge, not been reported by other authors.…”
Section: Discussioncontrasting
confidence: 43%
“…The degree of genomic instability parallels the degree of centrosome abnormalities in cell lines from breast , pancreas , prostate (Pihan et al, 2001), colon (Ghadimi et al, 2000), and cervix tumors (Skyldberg et al, 2001), from short-term culture of mouse mammary tumors (Montagna et al, 2002), and from SV40 ST overexpressing fibroblasts (Gaillard et al, 2001). Centrosome abnormalities were higher in high-grade prostate tumors (Pihan et al, 2001) and high-grade cervical tumors (Skyldberg et al, 2001) than in low-grade tumors. Centrosome amplification and chromosomal instability can be induced by over-expression of the centrosomal protein pericentrin and by over-expression of the centrosome kinase BTAK/STK15, suggesting that alternative mechanisms may lead to centrosome defects and consequent genomic instability (Pihan et al, 2001;Zhou et al, 1998).…”
Section: Correlation Of Centrosome Amplification Aneuploidy and Chromentioning
confidence: 99%
“…Strong support for a direct mechanistic link between centrosome amplification and CIN is suggested by the significant linear correlation between centrosome amplification and the rate of change in karyotype (CIN) seen in human breast tumors . Although such correlation alone does not necessarily imply cause and effect, these observations have led many authors to propose the hypothesis that centrosome amplification is the primary cause of genomic instability observed in most tumors (Gaillard et al, 2001;Lingle et al, 2002;Sato et al, 2001;Skyldberg et al, 2001). An alternative hypothesis has been proposed that chromosomal instability seen in cancer cells is caused by aneuploidy, that is that aneuploidy itself destabilizes the karyotype and thus initiates CIN leading to widespread heterogeneity in tumor cell phenotypes (Duesberg, 1999;Duesberg and Rasnick, 2000;Duesberg et al, 1998;Li et al, 2000).…”
Section: Correlation Of Centrosome Amplification Aneuploidy and Chromentioning
confidence: 99%
“…It has been shown that these multipolar mitoses are associated with abnormal numbers of mitotic spindle poles that are formed by centrosomes (Duensing et al, 2000). The incidence of cells with abnormal centrosome numbers increases in parallel with clinical progression during HPV-associated cervical carcinogenesis (Skyldberg et al, 2001).…”
Section: Hpv-16 E7 Induces Centrosome Duplication Errorsmentioning
confidence: 99%